Teaching and Learning Chemistry and Physics with a Laboratory Stations Model in a Flipped Classroom – A Preliminary Report - Coutinho, Isabel Ribau (Advances in Social Sciences Research Journal, 2022)
This research presents the efforts, to help students, hindered during the COVID19 pandemic, to learn chemistry. With the pandemic, Portuguese students that enrolled in the 10th grade in September 2021, had lower experience in the experimental work, since practical classes at school were suspended from mars 2019 to September 2021. So, students had difficulties in measuring or working with simple laboratory apparatus. They had difficulties in giving meaning to the experimental procedure, describing an observation, collecting data, analyzing data, and interpreting the results. In this context, it was necessary to have a learning and teaching approach different from the one they had in the last three years, to develop the skills they need. The first proposal was to use “Practical work by laboratory stations but it was not enough in the present context. So, a new learning and teaching project that blended digital tools/platforms and practical work in the laboratory was conceived. This learning and teaching project uses hybrid learning environments, based on practical work by laboratory stations, developed according to the collaborative Peer Instruction approach in a flipped classroom environment. The project's main goals were to develop scientific skills (like planning, collecting data observing and measuring, classifying, quantifying, predicting, controlling variables, interpreting, forming conclusions, and communicating) and increase their motivation to learn Chemistry and Physics. But also study the impact of the flipped classroom with laboratory stations, on motivation, self-regulation of learning, the perception of self-efficacy to self-regulate learning and the perceived instrumentality of the self-regulation process. The study population is the students enrolled in the 10th grade (upper secondary school), in a school near Lisbon. The research project was implemented in two classes: one class were subject to the new approach (one in the 10 grade), and the other maintained the regular practice (the control group). In this paper, the results from the first year will be presented and discussed. The data were collected in two moments, in September 2021 and June 2020. The preliminary results, of this research, show that laboratory classes with the flipped room increase not only the motivation and involvement in the learning process but also, the learning outcomes as students become more involved in the tasks.